Sodium-glucose cotransporter 2 inhibition does not reduce hepatic steatosis in overweight, insulin-resistant patients without type 2 diabetes - Marjot, T; Green, CJ; Charlton, CA; Cornfield, T; Hazlehurst, J; Moolla, A; White, S; Francis, J; Neubauer, S; Cobbold, JFL; Hodson, L; Tomlinson, JW (Wiley, 2019)
Background and Aim: Non-alcoholic fatty liver disease (NAFLD) is rapidly becoming the leading indication for liver transplant and is associated with increased cardiovascular and liver mortality, yet there are no licensed therapies. Sodium-glucose cotransporter 2 (SGLT2) inhibitors are widely used for their glucose-lowering effects in patients with type 2 diabetes (T2D). Preclinical models have suggested a beneficial impact on NAFLD, but clinical data are limited, and there are currently no data on patients without T2D. We aimed to investigate the impact of SGLT2 inhibition on NAFLD in overweight, nondiabetic patients and establish the effect these agents may have on the processes that regulate hepatic steatosis in vivo. Methods: We conducted an open-label, experimental medicine pilot study on insulin-resistant overweight/obese individuals (n = 10) using gold-standard noninvasive assessments of NAFLD phenotype, including magnetic resonance spectroscopy, two-step hyperinsulinemic euglycemic clamps, and stable isotope tracers to assess lipid and glucose metabolism. Investigations were performed before and after a 12-week treatment with the SGLT2 inhibitor, dapagliflozin. Results: Despite a body weight reduction of 4.4 kg, hepatic steatosis was unchanged following treatment. Hepatic glucose production increased, and there was impairment of glucose disposal during the low-dose insulin infusion. Although circulating, nonesterified, fatty acid levels did not change, the ability of insulin to suppress lipolysis was reduced. Conclusions: SGLT2 inhibition for 12 weeks does not improve hepatic steatosis in patients without T2D. Additional studies in patients with established T2D or impairments of fasting or postprandial glucose homeostasis are needed to determine whether SGLT2 inhibition represents a viable therapeutic strategy for NAFLD. (ClinicalTrials.gov Number NCT02696941).